The Mediation Effects of Motivation on the Influence of Self Efficacy Toward the Performance of Batik SMEs in Banyumas - Indrawiani, Tri Oktianti (ProBisnis : Jurnal Manajemen, 2025)
Engaged in the process of making Banyumasan batik. The purpose of this study is to analyze the effect of self-efficacy on performance through motivation as a mediation. The sample used in this studi were 80 employees at the SMEs Batik spread across the Banyumas Regency. This research uses Structural Equation Model Partial Least Square analysis technique using PLS software. The results of this study indicate that self-efficacy has not significantly effect on performance. Self efficacy has a significant and positive effect on motivation. Motivation has a significant and positive effect on performance. Motivation mediates the effect of self efficacy toward performance.